Pengaruh Pajak Daerah Dan Retribusi Daerah Terhadap Pendapatan Asli Daerah (PAD) Di Kota Bandung Tahun 2016-2020 - Jilan Haura Hanifa; Arry Irawan (Indonesian Accounting Research Journal, 2022)
This research aims to determine the effect of local taxes and local retribution on local revenue for the City of Bandung in 2016-2020 partially and simultaneously. This type of research is descriptive quantitative, using quantitative data types. Sources of data were obtained from the Badan Pengelola Pendapatan Daerah (BPPD) of Bandung City, namely data regarding the realization of local tax revenues, the realization of local retribution receipts and the realization of local revenue in Bandung City in 2016-2020. The analysis method used in this research is descriptive analysis, classical assumption test, multiple linear regression analysis, and hypothesis testing. The results indicate that Local tax and Local Retribution have a positive effect on Badung City's Local Revenue, either partially or simultaneously, for that it is necessary to optimize each component of the revenue to increase local income so it can fulfill the needs of the regional government.